Deciphering Adaptive Potential and Performance Traits in Cattle through Integrative Genomic Approaches - Panigrahi, Manjit; Rajawat, Divya; Nayak, Sonali Sonejita; Bose, Anal; Bharia, Nishu; Dutt, Triveni (Journal of Livestock Biodiversity, 2025)
Genomic tools and techniques have revolutionized our understanding of the genetic basis of adaptation and economically important traits in cattle and helped us to achieve sustainability in livestock breeding. This review highlights the amalgamation of genome-wide association studies (GWAS) and selection signature analyses to reveal candidate genes and genomic regions affecting disease resistance, productivity, climate resilience, and reproductive performance in cattle. The detection of trait-associated loci and selection footprints has been transformed by the use of high-density SNP arrays and next-generation sequencing techniques, like ddRAD-Seq and GBS. Case studies across diverse cattle populations, including Indian, African, and temperate ruminants, have revealed critical genomic regions bearing genes like HSPA1B, EPAS1, DGAT1, and BoLA, which are associated with immunity, thermotolerance, and economic performance. In addition to this, this paper highlights the urgent need to conserve India’s native cattle breeds and also advocates for proper in situ conservation strategies. The integration of molecular markers in GWAS and selection signature analyses have allowed precision breeding and improved the accuracy of candidate gene identification, facilitating genomic selection for climate resilience and productivity. This study also underlines the significance of genomically informed breeding programs in enhancing future livestock sustainability.